Crystal plasticity modeling of β phase deformation in Ti-6Al-4V. (24th August 2017) - Moore, John A; Barton, Nathan R; Florando, Jeff; Mulay, Rupalee; Kumar, Mukul
Abstract: Ti-6Al-4V is an alloy of titanium that dominates titanium usage in applications ranging from mass-produced consumer goods to high-end aerospace parts. The material's structure on a microscale is known to affect its mechanical properties but these effects are not fully understood. Specifically, this work will address the effects of low volume fraction intergranular β phase on Ti-6Al-4V's mechanical response during the transition from elastic to plastic deformation. A crystal plasticity-based finite element model is used to fully resolve the deformation of the β phase for the first time. This high fidelity model captures mechanisms difficult to access via experiments or lower fidelity models. The results are used to assess lower fidelity modeling assumptions and identify phenomena that have ramifications for failure of the material.